MANAJEMEN LALU LINTAS DI RUAS JALAN TEUKU UMAR BARAT DENPASAR BALI - Alexander Y. Koli; Anak Agung Gede Sumanjaya; Putu Aryastana (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2026)
Traffic congestion on Teuku Umar Barat Road is attributable to the road's location in the center of Denpasar, where there are very dense concentrations of shops. The purpose of this study is to analyze the performance of the Teuku Umar Barat road section in West Denpasar and to develop alternative solutions to address traffic congestion on the road. The method for calculating road section performance follows the Indonesian Road Capacity Guidelines 2023 to determine free-flow speed, capacity, and performance. The results of the analysis of the performance of the Teuku Umar Barat road section, with a 2/2 TT type of road, experienced performance problems with a degree of saturation value of 1.04, exceeding the road section performance eligibility requirements, which is ≤ 0.85, with the speed of passenger cars used being 26 Km/hour and the travel time used being 0.019 hours. After the implementation of traffic management, namely the implementation of the odd/even road system on the Teuku Umar Barat road from North to South and South to North, starting from the Marlboro intersection to the Gunung Salak intersection, the performance of the Teuku Umar Barat road improved with a decrease in the degree of saturation value to 0.48 and the speed of passenger cars used being 48 Km/hour. The travel time used with a segment length of 500 meters is 0.010 hours. The results of this study are expected to serve as a technical reference for local governments in the planning and management of traffic on urban road sections experiencing high levels of saturation.